The Efficacy and Flavonoid Levels in Sorghum Extracts of Super 2 Variety Under Various Levels of Drought Stress: Efikasi dan Kadar Flavonoid pada Ekstrak Sorgum Varietas Super 2 dengan Berbagai Tingkat Cekaman Kekeringan - Susilo, Edi; Pujiwati, Hesti (PendIPA Journal of Science Education, 2024)
Allelopathy-based bioherbicides for drought-stressed sorghum plants are a concrete step towards sustainable agriculture. This study aimed to look at the characteristics of seed germination and flavonoid levels of extracts that have experienced various levels of drought stress. Extract materials were prepared from June to August 2024 at Bengkulu University Greenhouse, Kandang Limun, Bengkulu City, and bioassay tests were conducted in August 2024 at Pematang Gubernur, Muara Bangkahulu, Bengkulu City. Flavonoid analysis was performed at the Integrated Research and Testing Laboratory (LPPT) of Gadjah Mada University in August 2024. This research used a completely randomized design (CRD) with one factor. One sorghum variety, Super 2, was planted with water stress treatment through watering patterns every day, every 2 days, every 3 days, every 4 days, and every 5 days. The experimental unit was a petri dish, and the experiment was repeated four times. The Petri dish bioassay method was applied in this experiment. Each petri dish was given 10 mL of aqueous extract, and 25 mung bean seeds were planted and incubated for three days. The results showed that the highest flavonoid levels were achieved by watering every 5 days (3625.00 µg/g) and the lowest every day (3165.26 µg/g). Sprout inhibition occurred due to sorghum water extract treated with watering patterns.